Performance characteristics of a new plastic explosive based on cis-1,3,4,6 -tetranitrooctahydroimidazo –[4,5-d] imidazole (BCHMX) and 3-nitro-1,2,4 -triazol-5-one (NTO) - Hussein, Ahmed Khaled Mohamed; Elbeih, Ahmed Ikhlas Mohamed; Zeman, Svatopluk (Univerzita Pardubice, 2017)
Plastic Explosives have several military and civilian applications. However, high performance with low sensitivity is difficult to obtain using an inert polymeric matrix. In this work, a new plastic explosive composition based on mixture of cis-1,3,4,6-tetranitrooctahydroimidazo-[4,5-d]imidazole (BCHMX) and 3-nitro-1,2,4-triazol-5-one (NTO) bonded by poly-dimethyl siloxane binder (BCHMX/NTO-Sil.),(44/44/12 by wt.), was prepared. For comparison, Two types of plastic explosives based on individual explosives, RDX (1,3,5-trinitro-1,3,5-triazinane or BCHMX, bonded by poly-dimethyl siloxane binder were studied in addition to the commercial available LOVA explosive TNTO (TNT 50% and NTO 50% by wt). Impact and friction sensitivities of these compositions as well as the individual explosives were determined. Experimental detonation velocity were performed for these compositions. Detonation characteristics were calculated using EXPLO5 program and compared with the experimental results. The results showed that BCHMX/NTO-Silicone has low sensitivity in the range of TNTO with higher detonation characteristic
Výkonnostní charakteristiky nové plastické trhaviny na bázi cis-1,3,4,6-tetranitrooktahydroimidazo [4,5-d] imidazolu (BCHMX) a 3-nitro-1,2,4-triazol-5-onu (NTO)
Keywords: Detonation characteristics; Performance; Sensitivity; BCHMX; NTO; detonační charakteristiky; výkonnost; citlivost; BCHMX; NTO